Legal Analysis of the TAPERA Programme in Increasing the Availability of Housing for Low-Income Communities in Indonesia Based on PP No. 21 of 2024 - Nasution, Emmi Rahmiwita; Solapari, Nuryati; Triastuti, Yuli (West Science Law and Human Rights, 2024)
This study conducts a normative juridical analysis of the TAPERA Programme, established by Government Regulation No. 21 of 2024, focusing on its efficacy in increasing the availability of housing for low-income communities in Indonesia. The TAPERA Programme aims to address housing affordability by encouraging savings among low-income individuals and providing financial assistance for housing needs. This research examines the legal framework, operational mechanisms, and regulatory environment of the programme, assessing its alignment with national housing policies and its potential impact. The findings indicate that while the TAPERA Programme holds significant promise due to its inclusive approach and emphasis on sustainability, challenges related to participation rates, implementation efficiency, and regulatory coherence need to be addressed. This analysis contributes to a deeper understanding of the legal and regulatory dimensions of housing policies in Indonesia, providing insights for policymakers and stakeholders involved in housing development for low-income communities.